Fairy tales for a fairer world - Deall, Kirsten (Perception Change Project, UN Office GenevaCH, 2016)
Links to the different sustainable development goals providing gateways for interactive online conversations between the readers, experts, specialists and public figures.Aims to to bring the issues to the forefront and to people across generations to facilitate an online discussion that concerns the entire world.